UTILIZATION OF THE LIBRARY AS A LEARNING RESOURCE CENTER FOR STUDENTS IN THE TECHNICAL IMPLEMENTATION UNIT (UPT) OF THE WIJAYA KUSUMA UNIVERSITY SURABAYA LIBRARY - BAKHTIYAR (CV KULTURA DIGITAL MEDIA, 2023)
Libraries have a very important role in supporting the learning process in higher education, because libraries are learning resource organizations by providing various information, which can be utilized by students to achieve brilliant academic achievements in higher education. The purpose of this research is to find out about the use of the library as a learning resource center for students at the Wijaya Kusuma University Library Technical Implementation Unit, Surabaya. This research is descriptive research, with research locations at the Faculty of Social and Political Sciences, Wijaya Kusuma University, Surabaya and taking 70 students as samples. The sampling technique in this research used purposive sampling with the focus of discussion being the use of libraries as learning resource centers. Data collection techniques use observation, interviews, questionnaires and documentation, while data processing techniques include: (1). Data Selection (2). Data Classification. (3). Data Tabulation. The data analysis technique uses qualitative descriptive analysis. The results of the research concluded that the use of the library as a learning resource center for students at the Faculty of Social and Political Sciences, Wijaya Kusuma University, Surabaya is at a good level.